Cost–benefit analysis of the COVID-19 vaccination model incorporating different infectivity reductions - Appiah, Raymond Fosu; Jin, Zhen; Yang, Junyuan; Asamoah, Joshua Kiddy K. (Frontiers in Physics, 2024)
The spread and control of COVID-19 is a worldwide economical and medical burden to public health. It is imperative to probe the effect of vaccination and infectivity reductions in minimizing the impact of COVID-19. Therefore, we analyze a mathematical model incorporating different infectivity reductions. This work provides the most economical and effective control methods in reducing the impact of COVID-19. Using data from Ghana as a sample size, we study the sensitivity of the parameters to estimate contributions of the transmission routes to the effective reproduction number 𝑅 𝑒 . We also devise optimal interventions with cost-benefit analysis that aim to maximize outcomes while minimizing COVID-19 incidences by deploying cost-effectiveness, and optimization techniques. The outcomes of this work contribute to a better understanding COVID-19 epidemiology and provide insights into implementing interventions needed to minimize COVID-19 burden in similar settings worldwide.